Fostering the entrepreneurial ecosystem: The roles of government agencies in Malaysia - Wan Yusoff, Wan Fauziah; Kian, Tan Shen; Ahmad, Abdul Razak; Jusoh, Nuraniza Quantaniah (American Scientific Publishers, 2018)
It has been acknowledged that the government plays significant roles in the entrepreneurship development of many countries including Malaysia. This paper analyzed and summarized the roles of Malaysian government in fostering the Entrepreneurship Ecosystem of the country. The roles of ten governmental agencies that are involved in entrepreneurship development have been reviewed in relation to the six domains of entrepreneurial ecosystem; policy, finance, culture, business support and infrastructure, human capital and market. The reviews revealed that the ten agencies are fully involved in the six domains of entrepreneurial ecosystem. In particular, in term of providing advisory and financial supports, human capital, developing entrepreneurship policies and business networking. However, as the roles of the agencies found to be overlapping from one to another it is suggested that the coordination roles among the agencies is needed to enhance the quality and effectiveness of the entrepreneurship ecosystem of the country.